A new approach to preparing Bi2Zr2O7 photocatalysts for dye degradation. (19th January 2018) - Luo, Yijia; Cao, Liyun; Huang, Jianfeng; Feng, Liangliang; Yao, Chunyan
Abstract: A new synthetic route is presented to prepared pure Bi2 Zr2 O7 material, in which a NaNO3 /KNO3 molten salt is used to obtain the resulting Bi2 Zr2 O7 at a relatively low temperature of 400 °C under atmospheric pressure. Powder x-ray diffraction confirmed the structure type and purity of the as-prepared sample, and further revealed that a single-source Bi(OH)3 · Zr(OH)4 · n H2 O complex precursor plays a crucial role to synthesize Bi2 Zr2 O7 nanocrystals. Scanning electron microscope and transmission electron microscope show the morphologies and sizes of Bi2 Zr2 O7 crystal in detail, and UV–vis diffuse reflectance measurements evidenced the wide light absorption range. Furthermore, the as-synthesized Bi2 Zr2 O7 with smaller particle size and larger specific surface area exhibit superior photocatalytic activities compared with the sample obtained without adding molten salts.